Released Parasite-Derived Kinases as Novel Targets for Antiparasitic Therapies - Silvestre, Anne; Shintre, Sharvani Shrinivas; Rachidi, Najma (Frontiers in Cellular and Infection Microbiology, 2022)
The efficient manipulation of their host cell is an essential feature of successful intracellular parasites. Most molecular mechanisms governing the subversion of host cell by protozoan parasites involve the release of parasite-derived molecules into the host cell cytoplasm and direct interaction with host proteins. Among the parasitic released proteins, the protein kinases are particularly important as they govern the subversion of important host pathways, such as signalling or metabolic pathways. These enzymes, which catalyse the transfer of a phosphate group from ATP onto serine, threonine, tyrosine or histidine residues to covalently modify proteins, are involved in numerous essential biological processes such as cell cycle or transport. One major difference characterizes the protozoan parasite kinome from that of their host cells, the presence of specific groups of PKs such as NEK, FIKK or ROPK that were duplicated from an ancestor gene. Although little is known about the role of the released parasitic PKs in the host cell, they hijack host cellular pathways such as signal transduction or apoptosis, which are essential for immune response evasion as well as parasite survival and development. Here we present the current knowledge on released protozoan kinases and their involvement in host-pathogen interactions. We highlight the knowledge gaps remaining to consider those released kinases involved in host signalling subversion, as antiparasitic drug targets.